Teaching Introduction to Theatrical Design : A Process Based Syllabus in Costumes, Scenery, and Lighting /: A Process Based Syllabus in Costumes, Scenery, and Lighting. (2016) - Appleton, Eric; Lyons, Tracey
No abstract available